Peasant agro-food territories: Agroecology and food sovereignty in response to extractivism in the Colombian Massif - Rosero, Jerson; Buitrago, Oscar; Matarán, Alberto (Revista de Ciencias Agrícolas, 2025)
The response of the peasant movement in the Colombian Massif to the exclusionary neoliberal model characterizing the Colombian State—marked by land concentration, dispossession, and the invisibility of rural communities—was analyzed. Peasant Agro-Food Territories (TECAM) emerge as a proposal of resistance against extractivism, promoting social justice, agroecology, and food sovereignty. These rhizomatic and revolutionary strategies aim to reconfigure the territory and challenge power relations, fostering an alternative model of territorial planning and peasant autonomy. The study employed interviews, document analysis, and historical memory workshops to identify key milestones from 1987 to 2024 and to analyze agency strategies using conceptual categories such as rhizomes, lines of flight, and molecular revolution. Data were coded and analyzed using ATLAS.ti software. The results highlight significant milestones such as the creation of the Plan de Vida Agua y Dignidad (Water and Dignity Life Plan), agro-environmental schools, and popular consultations against mega-mining. These findings demonstrate the communities’ capacity to organize and confront extractivist and neoliberal policies. TECAM represents an endogenous alternative that challenges traditional power structures and proposes new paradigms of territorial justice and ecological sustainability. It reflects the peasantry’s ability to drive profound sociopolitical transformations, prioritizing common goods and dignified life over the hegemonic logic of capitalist development.